Effects of dynamic apnea training on diving bradycardia and short distance swimming performance - Mulder, E. R.; Holmström, P. K.; Schagatay, E. K. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Apnea training enhances bradycardia and improves competitive apnea performance and has been proposed as a training method for other sports, such as swimming. We evaluated the effects of apneic underwater swimming, i.e., dynamic apnea (DYN), in 9 competitive swimmers (TR) who completed ten DYN sessions over 2 weeks. METHODS: TR performed pre- and post-training tests including a static apnea test with continuous heart rate (HR) and peripheral oxygen saturation measurements, all-out 50m and 100m freestyle tests and an all-out DYN test. Control groups were competitive swimmers (SC; N.=10) that trained swimming without DYN, and a non-swimmer group (AC; N.=10) performing only static apnea tests. RESULTS: Post-training, TR mean±SD time for 50 m freestyle improved from 25.51±2.01 s to 24.64±2.02 s (P<0.01) and for 100m from 55.5±4.2 s to 54.1±4.4 s (P<0.05). SC also improved their 100m time from 56.7±3.3 s to 56.0±3.1 s (P<0.01; P=0.07 between groups). Only TR performed DYN tests; DYN distance increased from 62.1±11.5 m to 70.9±18.9 m (P<0.05) while DYN speed decreased from 0.74±0.14m/s to 0.64±0.18 m/s (P<0.01). Static apnea duration did not change in any of the groups, but HR-reduction was enhanced post-training only in TR (24.8±14.8% to 31.1±10.9%, P<0.01; P<0.001 between groups). CONCLUSIONS: We conclude that 2 weeks of DYN training enhanced DYN performance, which may be caused by the enhanced apnea-induced diving bradycardia. Further research is required to determine whether DYN training enhances short distance freestyle swimming performance.